Diagnosis and treatment of postpartum hemorrhage. - Calle, Andrés (2015)
Postpartum hemorrhage is a severe obstetrical complication that produces almost one third of maternal deaths, especially in underdeveloped countries. Multiple complications can produce this type of clinical scenario. Nevertheless uterine atony, placental birth alterations, and cervical and vaginal tears are doubtlessly those of greater prevalence. Their opportune treatment and timely use of effective measures are indispensable and fundamental to avoid maternal death. To know about populations at risk and triggering factors is fundamental, because this pathology is highly preventable and we must be prepared to face this type of complications.